Discovering a heritage - Unes, Wolney (Revista UFG, 2017)
The decision about what to preserve is an active choice. The heritage, facts or people which are chosen will live on, rescued from the darkness of oblivion. It is the quest for eternal life. Every day we must decide what to preserve, what heritage we want to maintain as symbols of our existence. This entire heritage forms our cultural canon and concepts such as authorship, fidelity and originality can be used to define it. In times of emphasis on the receiver, views and readings change, and artifacts from the past take on a new dimension. Should the way we perceive this heritage change, then the set of prescribed and recommended heritage must also change. So against this background, this short article sets out to discuss the significance of incorporating the Art Déco heritage into the national Brazilian artistic and architectural canon. But, before doing so, a quick reminder about memory would be appropriate. (...)